Phyllanthus Niruri L. Exerts Protective Effects Against the Calcium Oxalate-Induced Renal Injury via Ellgic Acid - Li, Mao-Ting; Liu, Lu-Lu; Zhou, Qi; Huang, Lin-Xi; Shi, Yu-Xuan; Hou, Jie-Bin; Lu, Hong-Tao; Yu, Bing; Chen, Wei; Guo, Zhi-Yong (Frontiers in Pharmacology, 2022)
Background: Urolithiasis or kidney stones is a common and frequently occurring renal disease; calcium oxalate (CaOx) crystals are responsible for 80% of urolithiasis cases. Phyllanthus niruri L. (PN) has been used to treat urolithiasis. This study aimed to determine the potential protective effects and molecular mechanism of PN on calcium oxalate-induced renal injury. Methods: Microarray data sets were generated from the calcium oxalate-induced renal injury model of HK-2 cells and potential disease-related targets were identified. Network pharmacology was employed to identify drug-related targets of PN and construct the active ingredient-target network. Finally, the putative therapeutic targets and active ingredients of PN were verified in vitro and in vivo. Results: A total of 20 active ingredients in PN, 2428 drug-related targets, and 127 disease-related targets were identified. According to network pharmacology analysis, HMGCS1, SQLE, and SCD were identified as predicted therapeutic target and ellagic acid (EA) was identified as the active ingredient by molecular docking analysis. The increased expression of SQLE, SCD, and HMGCS1 due to calcium oxalate-induced renal injury in HK-2 cells was found to be significantly inhibited by EA. Immunohistochemical in mice also showed that the levels of SQLE, SCD, and HMGCS1 were remarkably restored after EA treatment. Conclusions: EA is the active ingredient in PN responsible for its protective effects against CaOx-induced renal injury. SQLE, SCD, and HMGCS1 are putative therapeutic targets of EA.